Gamifying SQL Learning: Strategies, Impact, and Trends in Higher Education - Sandra Del-Pozo-Arcos; Antonio Balderas (Interaction Design and Architecture(s))
This article presents a study that combines a systematic mapping of the use of gamification in SQL learning with a case study conducted in a database course in higher education. The research addresses the convergence between gamification and SQL learning by evaluating and categorizing existing literature and integrating this review with the analysis of a specific implementation of gamification techniques. Various gamification strategies and approaches used in educational settings to facilitate the understanding and mastery of SQL are examined, highlighting effective practices and areas of opportunity. It also identifies emerging trends, challenges and research gaps, providing a comprehensive overview of gamification in database education. This blend of theoretical analysis and case study aims to inform educators, researchers and practitioners about the current state of gamification in SQL learning, and to encourage critical reflection and innovation to improve pedagogical practice in this specific area.